Overexpression of WRINKLED1 improves the weight and oil content in seeds of flax (Linum usitatissimum L.) - Li, Wenjuan; Wang, Limin; Qi, Yanni; Xie, Yaping; Zhao, Wei; Dang, Zhao; Zhang, Jianping (Frontiers in Plant Science, 2022)
Seeds of flax (Linum usitatissimum L.) are highly rich in both oil and linolenic acid (LIN). It is crucial for flax agricultural production to identify positive regulators of fatty acid biosynthesis. In this study, we find that WRINKLED1 transcription factors play important positive roles during flax seed oil accumulation. Two WRINKLED1 genes, LuWRI1a and LuWRI1b, were cloned from flax, and LuWRI1a was found be expressed predominantly in developing seeds during maturation. Overexpression of LuWRI1a increased seed size, weight, and oil content in Arabidopsis and increased seed storage oil content in transgenic flax without affecting seed production or seed oil quality. The rise in oil content in transgenic flax seeds was primarily attributable to the increase in seed weight, according to a correlational analysis. Furthermore, overexpression or interference of LuWRI1a upregulated the expression of genes in the fatty acid biosynthesis pathway and LAFL genes, and the expression level of WRI1 was highly significantly positively associated between L1L, LEC1, and BCCP2. Our findings give a theoretical scientific foundation for the future application of genetic engineering to enhance the oil content of plant seeds.